2017
DOI: 10.1002/osp4.116
|View full text |Cite
|
Sign up to set email alerts
|

Real-world weight change among patients treated with glucagon-like peptide-1 receptor agonist, dipeptidyl peptidase-4 inhibitor and sulfonylureas for type 2 diabetes and the influence of medication adherence

Abstract: SummaryAimsThe study aims to examine real‐world weight change and the role of medication adherence among patients with type 2 diabetes who initiated one of three drug classes: glucagon‐like peptide‐1 receptor agonist (GLP‐1RA), dipeptidyl peptidase‐4 inhibitor (DPP4) and sulfonylureas (SUs).Materials and methodsA cohort of patients initiating one of the three drug classes was selected from a large US database of integrated electronic medical record and administrative claims. Adherence was defined as per cent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…In the real‐world clinical practice setting, this consistency in efficacy with dulaglutide 1.5 mg treatment regardless of BMI is important for patients and healthcare professionals, as GLP‐1 RA treatments are most frequently prescribed to patients with a BMI of ≥35 kg/m 2 . As the analyzed population included patients with a BMI of <30 kg/m 2 (36% overall), these data also suggest that dulaglutide 1.5 mg treatment is efficacious for patients regardless of BMI.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…In the real‐world clinical practice setting, this consistency in efficacy with dulaglutide 1.5 mg treatment regardless of BMI is important for patients and healthcare professionals, as GLP‐1 RA treatments are most frequently prescribed to patients with a BMI of ≥35 kg/m 2 . As the analyzed population included patients with a BMI of <30 kg/m 2 (36% overall), these data also suggest that dulaglutide 1.5 mg treatment is efficacious for patients regardless of BMI.…”
Section: Discussionmentioning
confidence: 78%
“…AW, AWARD study; BMI, body mass index; CI, confidence interval; DU, dulaglutide; ITT, intent to treat population; LS mean, least-squares mean; W, week for patients and healthcare professionals, as GLP-1 RA treatments are most frequently prescribed to patients with a BMI of ≥35 kg/m 2 . [7][8][9] As the analyzed population included patients with a BMI of <30 kg/m 2 (36% overall), these data also suggest that dulaglutide Weight management is an important part of managing type 2 diabetes. A post hoc analysis of patient data from the AWARD-1 to -6 studies investigated the relationship between weight change, HbA1c, and the effect of baseline characteristics on weight and HbA1c responses.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Weight gain has also been reported as a side effect. This could confound any attempt to link the drug to cancer . A meta‐analysis of 72 studies of sulfonylureas found a 20% increased cancer risk (although with high heterogeneity: I 2 =95%), but in an analysis that comprised only the 38 RCTs, the association did not persist .…”
Section: Types Of Antidiabetes Medicationmentioning
confidence: 99%